Modernisme Dan Pruitanisme Dalam Islam - Amon Jaya; Nadia Eva Gelista; Zahratul Habiba; Agus Rifki Ridwan (JURNAL ILMIAH NUSANTARA, 2025)
Modernism and puritanism in Islam are two approaches that have had a significant influence on the development of Muslim religious thought and practice. Modernism in Islam refers to a movement that aims to interpret religious teachings in accordance with the context of the times, emphasizing rationality, science, and openness to social change. The movement often sought to bridge traditional values with the demands of modernity, giving birth to figures such as Muhammad Abduh and Jamaluddin al-Afghani who pushed for educational, legal and social reforms. In contrast, puritanism in Islam focuses on purifying religious teachings from practices that are considered deviant or bid'ah, and returning to the primary sources, namely the Qur'an and Sunnah. Puritanism is often associated with movements that emphasize literality in understanding religious texts and reject outside cultural influences that are considered to undermine the purity of Islam. An example of a puritanical movement is Wahhabism that developed in the Arabian Peninsula. These two approaches often interact dynamically, both in the form of dialog and conflict, in an effort to find the best format to maintain the relevance of Islam in the modern era. This research analyzes the ideological roots, main figures, and practical implications of modernism and puritanism in shaping Muslim religious identity. By understanding these two movements, it is hoped to create a broader insight in managing the diversity of perspectives in Islam, so that it can be the basis for the development of inclusive and progressive Islamic thought.